A new electrocardiographic sign in infants and children with hypothyroidism and its differentiation from similar electrocardiographic patterns - Ertuğrul, Ali (The Turkish Journal of Pediatrics, 1965)
Dome-shaped T waves and the absence of the ST segment combined with generalized low voltage of all complexes with bradycardia are specific signs of hypothyroidism. Views of some electrocardiograms of hypothyroid patients remind one of the silhouette of a mosque. The dome-shaped T wave immediately after the QRS complex without an ST segment resembles a minaret with a dome. This observation has been present in 16 of 45 hypothyroid patients. In 13 patients the electrocardiographic changes were suggestive of hypothyroidism but not diagnostic. The electrocardiograms of the remaining 16 patients had only some non-specific changes.I found that when this change is present, it is diagnostic, but when it is not present, it is not necessarily indicative of the absence of hypothyroidism.On rare occasions, electrocardiographic findings in different types of myocarditis and electrolyte disturbances might have an appearance somewhat resembling these changes. However, I have not been able to find these characteristic electrocardiographic changes in any other disease except hypothyroidism in infants and children.